Progressive Evaluation of Ischemic Occlusion in a Macaque Monkey with Sudden Exacerbation of Infarction During Acute Stroke: A Case Report - Chun-Xia Li; Xiaodong Zhang (Veterinary Sciences)
Early neurological deterioration is associated with poor functional outcomes in stroke patients, but the underlying mechanisms remain unclear. This study aims to understand the progression of stroke-related brain damage using a rhesus monkey model with ischemic occlusion. Multiparameter MRI was used to monitor the progressive evolution of the brain lesion following stroke. Resting-state functional MRI, dynamic susceptibility contrast perfusion MRI, diffusion tensor imaging, and T1- and T2-weighted scans were acquired prior to surgery and at 4–6 h, 48 h, and 96 h following the stroke. The results revealed a sudden increase in infarction volume after the hyper-acute phase but before 48 h on diffusion-weighted imaging (DWI), with a slight extension by 96 h. Lower relative cerebral blood flow (CBF) and time to maximum (Tmax) prior to the stroke, along with a progressive decrease post-stroke, were observed when compared to other stroke monkeys in the same cohort. Functional connectivity (FC) in the ipsilesional secondary somatosensory cortex (S2) and primary motor cortex (M1) exhibited an immediate decline on Day 0 compared to baseline and followed by a slight increase on Day 2 and a further decrease on Day 4. These findings provide valuable insights into infarction progression, emphasizing the critical role of collateral circulation and its impact on early neurological deterioration during acute stroke.